Effectiveness of the ten-valent pneumococcal Haemophilus influenzae protein D conjugate vaccine (PHiD-CV10) against all respiratory tract infections in children under two years of age. Issue 22 (16th May 2019) - Karppinen, Sinikka; Toivonen, Laura; Schuez-Havupalo, Linnea; Teros-Jaakkola, Tamara; Waris, Matti; Auranen, Kari; Palmu, Arto A.; Peltola, Ville
Highlights: PHiD-CV10 vaccine was associated with a 12% reduction in all respiratory tract infections (RTIs) in children. The effectiveness of PHiD-CV10 was seen in RTIs with and without acute otitis media. Rhinovirus was the most common causative agent of RTIs. Pneumococcal conjugate vaccines may provide protection against all-cause RTIs in children. Abstract: Background: Pneumococcal conjugate vaccines reduce the incidence of invasive pneumococcal diseases, pneumonia, acute otitis media (AOM), and antimicrobial prescriptions in children. We investigated the effectiveness of at least one dose of the ten-valent pneumococcal Haemophilus influenzae protein D conjugate vaccine (PHiD-CV10; GSK) against respiratory tract infections (RTIs) in children under two years of age. Methods: 424 children enrolled in a cluster–randomized, double-blind Finnish Invasive Pneumococcal disease (FinIP) vaccine trial during the years 2009–2010 were actively followed in a prospective cohort study (STEPS study) for RTIs from birth to two years of age. Children received the PHiD-CV10 vaccine, or a control vaccine (hepatitis A or B vaccine) according to an age-specific schedule. Data on RTIs were collected by symptom diaries, clinic visits, an electronic registry on hospitalizations, and by nasal swab samples analyzed for respiratory viruses. We estimated the vaccine effectiveness against all RTI episodes and RTI episodes with or without AOM by comparing the corresponding incidence rates between PHiD-CV10 vaccinated and control children, adjusted for presence of siblings and cluster as a random effect. Results: A total of 3193 RTI episodes were documented after the first vaccination in 368 children with all data available. The majority of the illnesses were upper RTIs caused by rhinovirus. The PHiD-CV10-vaccinated children had lower mean annual rates of all RTI episodes (6.4; 95% confidence interval [CI], 6.0–6.8) and RTI episodes with AOM (1.0; 95% CI, 0.9–1.2) as compared to the control children (7.4; 95% CI, 6.8–8.0 and 1.3; 95% CI, 1.1–1.6, respectively). The vaccine effectiveness was 12% (95% CI, 2–22%) against all RTIs, 23% (95% CI, 0–40%) against RTIs with AOM, and 10% (95% CI, 0–19%) against RTIs without AOM. Conclusions: Vaccination with PHiD-CV10 resulted in lower rates of RTIs in children under two years of age compared to children vaccinated with control vaccine.